2019
DOI: 10.1200/jco.2019.37.15_suppl.4003
|View full text |Cite
|
Sign up to set email alerts
|

ABC-06 | A randomised phase III, multi-centre, open-label study of active symptom control (ASC) alone or ASC with oxaliplatin / 5-FU chemotherapy (ASC+mFOLFOX) for patients (pts) with locally advanced / metastatic biliary tract cancers (ABC) previously-treated with cisplatin/gemcitabine (CisGem) chemotherapy.

Abstract: 4003 Background: Level A evidence supports use of CisGem as first-line chemotherapy for ABC; no robust evidence is available for second-line chemotherapy. Methods: Pts diagnosed with ABC with disease progression after prior CisGem were randomised (1:1) to either ASC+mFOLFOX or ASC. Randomisation was stratified by serum albumin levels ( < 35 vs ≥35 g/L), platinum sensitivity (determined from first-line CisGem) and disease extent (locally advanced vs metastatic). Pts with ECOG PS0-1, adequate haematological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
186
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(199 citation statements)
references
References 0 publications
7
186
0
6
Order By: Relevance
“…In previous studies that adopted pembrolizumab as a salvage therapy for pretreated BTC patients including ours, pembrolizumab showed a modest efficacy with ORR of 6%-13%, median PFS of 1.5-2.0 months, and median OS of 4.3-7.3 months. Fluoropyrimidine-based chemotherapy showed median PFS of 1.9 months and OS of 6.5 months in a previous retrospective analysis [29], while mFOLFOX showed median PFS and OS of 4.0 and 6.2 months, respectively; in a recent randomized phase 3 ABC-06 trial after progression on firstline GemCis [5], current evidences with pembrolizumab are not compelling for its use as salvage therapy in overall BTC patients. However, pembrolizumab may have clinical relevance in the management of refractory BTC patients in terms of long DOR (median DOR of 6.3 months in our study, and 2-year DOR of 67% and 50% in the KEYNOTE-028 and KEY-NOTE-158 studies, respectively) and better safety profile compared with mFOLFOX (grades 3-4 AEs: 14%-17% in KEYNOTE-028 and KEYNOTE-158 studies vs. 59% in the ABC-06 trial).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous studies that adopted pembrolizumab as a salvage therapy for pretreated BTC patients including ours, pembrolizumab showed a modest efficacy with ORR of 6%-13%, median PFS of 1.5-2.0 months, and median OS of 4.3-7.3 months. Fluoropyrimidine-based chemotherapy showed median PFS of 1.9 months and OS of 6.5 months in a previous retrospective analysis [29], while mFOLFOX showed median PFS and OS of 4.0 and 6.2 months, respectively; in a recent randomized phase 3 ABC-06 trial after progression on firstline GemCis [5], current evidences with pembrolizumab are not compelling for its use as salvage therapy in overall BTC patients. However, pembrolizumab may have clinical relevance in the management of refractory BTC patients in terms of long DOR (median DOR of 6.3 months in our study, and 2-year DOR of 67% and 50% in the KEYNOTE-028 and KEY-NOTE-158 studies, respectively) and better safety profile compared with mFOLFOX (grades 3-4 AEs: 14%-17% in KEYNOTE-028 and KEYNOTE-158 studies vs. 59% in the ABC-06 trial).…”
Section: Discussionmentioning
confidence: 93%
“…Complete surgical resection, which is the only curative treatment, is available for only a minority of patients and is hindered by a low overall 5-year survival rate and high rate of tumor recurrence [1,4]. For patients with advanced BTC, the phase III ABC-02 and ABC-06 trials showed the clinical efficacy of gemcitabine plus cisplatin (GemCis) and oxaliplatin plus fluoropyrimidine (mFOLFOX) as first-line therapy and second-line therapy, respectively [5,6]. However, the survival outcomes remain dismal with a median overall survival (OS) of < 1 year, and none of the targeted agents have been approved for treatment of BTC [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The randomized, phase 3 ABC-06 trial recently reported a median overall survival of 6.2 months for patients with ABC treated with FOLFOX as second-line therapy at 20 centers across the United Kingdom, which achieved a small but significant improvement over active symptom control (hazard ratio, 0.69; 95% CI, 0.50-0.97; P = .031). 13 Although the absolute survival outcomes were shorter than those in our retrospective analysis and perhaps reflective of the selection bias inherent to tertiary referral center populations, as discussed previously, the PFS was similarly modest: it measured 4.0 months for FOLFOX (95% CI, 3.2-5.0 months) and reinforced the need for more efficacious therapies for ABC after first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The first randomized phase III study ABC-06 randomized 162 patients to active symptom control (i.e., antibiotic therapy, corticorticosteroid therapy, biliary drainage) and FOLFOX regimen (oxaliplatin/fluorouracil) after cisplatin-gemcitabine failure. Although the reported median survival benefit of FOLFOX regimen over active symptom control was small (5.3 versus 6.2 months, adjusted HR 0.69), the FOLFOX regimen obtained more significant survival rate at 6 (35.5% versus 50.6%) and 12 months (11.4% versus 25.9%) [32]. The available studies globally support the use of second-line therapy in young and fit patients.…”
Section: Chemotherapy For Metastatic Disease: First and Second Linesmentioning
confidence: 94%